Residual effects of cannabis on attention toward and awareness of emotional facial expressions: event-related potential studies - Torrence, Robert D., author; Rojas, Donald C., advisor; Troup, Lucy J., advisor; Nerger, Janice, committee member; Burzynska, Agnieszka, committee member (Colorado State University. Libraries, 2018)
Cannabis use has increased since legalization in various states within the United States of America. Although much of the research on the neurological and psychological effects of cannabis has been on non-human animals, the current research suggests that it can have anxiolytic effects but also decrease some cognitive functioning (e.g. memory, emotional processing, etc.). Individuals with high anxiety has been suggested to have increased attentional bias towards threat-related stimuli. The purpose of the current two studies was to examine the residual effects cannabis has on attentional bias towards and awareness of emotional facial expressions. Both experiments used event-related potential (ERP) to measure brain activity related to attentional processing. Experiment 1 used a dot-probe task with fearful and neutral facial expression to examine attentional bias. The second experiment used a backward masking paradigm to restrict awareness of facial expressions (i.e. fearful, happy, and neutral). The results indicated that cannabis use was associated with differences in attentional processing. Specifically, experiment 1 suggested cannabis users had reduced attentional bias towards fearful facial expressions as compared to non-users. The results from experiment 2 suggested an opposite effect, cannabis users had increased processing of emotional facial expressions. An explanation of the difference in results is the cannabis users in experiment 1 used less frequently than users in experiment 2. The results of both studies suggested cannabis use has an inverse relationship with anxiety related attentional processing of emotional expressions.
Keywords: attentional bias; ERP; anxiety; faces; cannabis